HETEROSIS STUDIES FOR YIELD COMPONENT TRAITS AND QUALITY IN SPRING WHEAT (TRITICUM AESTIVUM L.) - DINESH KUMAR; S. A. KERKHI (The Bioscan, 2014)
A study was conducted to estimate the extent of heterosis for yield and some quality in the experiment was planted in a RCBD with three replication and 45 F1 crosses along with 10 diverse genotypes by diallel mating design in spring wheat. The estimation of high degree of heterosis in certain cross combination namely, DBW 58 × DBW 17 followed by MP 1236 × PBW 550, PBW 550 × PBW 590, PBW 550 × HD 2687, WH 1094 × PBW 590, MP 1236 × WH 1094 and PBW 590 × WH 711 which may be exploited for developing hybrids with better yield and quality in spring wheat. Out of these 11 crosses, the cross PBW 550 × PBW 373 and MP 1236 × PBW 373 which showed significant sca effect with good per se performance for grain yield may be used in cross breeding programme and might be expected to give transgressive segregants in F2 as these two crosses are having the parents with low × high and high × high gca effect.